Hemorrhage Risk of Cavernous Malformation - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2012)
Researchers at the Mayo Clinic, Rochester, MN reviewed the records and radiograph data of 292 patients (47.3% male) seen between 1989 and 1999 with a diagnosis of intracerebral cavernous malformation (ICM).